L'adulte au moment du pré-mitan: son vécu au travail selon les classes sociales - Riverin-Simard, Danielle (Canadian Journal of Counselling and Psychotherapy, 2011)
The aim of this article is to describe and compare the occupational experience of pre middleaged adults according to their background of upper, middle, or lower socio-economic class. For this purpose 73 subjects in the age range 33-37 years were interviewed in the administrative region 03 (Québec). Subjects were selected randomly and divided according to the following variables: socio-economic class, sex, and occupational sector. The findings indicate that the pre middle-aged adult struggles with an already predetermined occupational direction. As the case may be, he attempts to gain control of its direction: to surmount it (low socio-economic class) or to advance on it (upper socio-economic class).